Adverse Drug Reaction – A Significant Cause of Morbidity and Mortality - Parihar, Madhu; Kapoor, Ritu; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2021)
An Adverse Drug Reaction (ADR) as “An appreciably harmful or unpleasant reaction” after taking a medicine at normal doses, during normal use. Adverse drug reactions are a significant cause of morbidity and mortality and it is considered non preventable. The term Adverse Drug Effect is convertible with Adverse Drug Reaction. The meaning of ADR is different from the word side effect because side effects are beneficial as well as harmful. The field under which ADR is studied is known as Pharmacovigilance. An Adverse Drug Event (ADE) is an injury resulting from medical intervention related to a drug. The Adverse drug reactions are classified into six types. Timing, the pattern of illness, the results of investigations, and rechallenge can help idiosyncrasy causality to a suspected adverse drug reaction. If possible in management, you can stop that drug and treat its effects. Suspicious adverse drug reactions should be reported so that such cases can be prevented in the future.